Robotic-Assisted Surgery for Benign Urological Conditions - Declan G. Murphy; Ben J. Challacombe; Lail-U-Mah Zaheer; M. Shamim Khan; Prokar Dasgupta (The Scientific World Journal, 2006)
Robotic technology for use in surgery has advanced considerably in the past 10 years. This has become particularly apparent in urology where robotic-assisted radical prostatectomy using the da VinciTM surgical system (Intuitive Surgical, CA) has become very popular. The use of robotic assistance for benign urological procedures is less well documented. This article considers the current robotic technology and reviews the situation with regard to robotic surgery for benign urological conditions.